2018
DOI: 10.5694/mja18.00227
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Molecular Screening and Therapeutics (MoST): a framework for multiple, parallel signal‐seeking studies of targeted therapies for rare and neglected cancers

Abstract: Background: Precision medicine aims to link molecular targets in tumours with corresponding therapies, particularly for patients with rare cancers. Innovative approaches are needed to translate molecular opportunities into clinical care. The Cancer Molecular Screening and Therapeutics (MoST) program employs a molecular screening platform to identify molecular changes of therapeutic relevance (actionable changes) and a master protocol for multiple, parallel signal‐seeking clinical substudies, focused on therapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 17 publications
(31 reference statements)
0
40
0
Order By: Relevance
“…Participants were recruited to the Molecular Screening and Therapeutics (MoST) cancer genomic study, which is recruiting adult patients with pathologically confirmed advanced or metastatic solid cancers (of any histological type) who have exhausted therapeutic options. 6 Participants undergo MP and, if an actionable variant is found, are enrolled in a related therapeutic trial if available. Participants can elect to receive actionable, non-actionable and/or germline results at the time of consent, and to allow germline results to be returned to family members in the event of the participant's death.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were recruited to the Molecular Screening and Therapeutics (MoST) cancer genomic study, which is recruiting adult patients with pathologically confirmed advanced or metastatic solid cancers (of any histological type) who have exhausted therapeutic options. 6 Participants undergo MP and, if an actionable variant is found, are enrolled in a related therapeutic trial if available. Participants can elect to receive actionable, non-actionable and/or germline results at the time of consent, and to allow germline results to be returned to family members in the event of the participant's death.…”
Section: Methodsmentioning
confidence: 99%
“…This mixed-methods study aimed to examine the preferences for receiving results of advanced cancer patients who were actually undergoing MP (under a research protocol) in order to access novel therapies. 6…”
Section: Introductionmentioning
confidence: 99%
“…The Molecular Screening and Therapeutics (MoST) Program is a study underway at the Garvan Institute of Medical Research in Sydney, Australia [12]. It is recruiting 1,000 adult participants with pathologically confirmed advanced or metastatic solid cancer, with a particular focus on rare cancer.…”
Section: Methodsmentioning
confidence: 99%
“…Details of inclusion and exclusion criteria for MoST are reported in full in the MoST protocol paper [12]. In summary, the target population comprises adult participants with pathologically confirmed advanced or metastatic solid cancers of any histological type, either during or after their last line of effective therapy; participants have Eastern Cooperative Oncology Group (ECOG) Performance Status 0, 1 or 2; and have sufficient accessible tissue for molecular profiling.…”
Section: Methodsmentioning
confidence: 99%
“…With tremendous progress in cancer biology and molecular diagnostics, cancer treatment is increasingly reliant on tumour molecular profiling to inform rational treatment decisions. To date, large precision oncology programs have harnessed the advances in genomic technology to inform design of a plethora of molecular matched trials [1][2][3][4][5][6][7][8]. Molecular testing, typically based on DNA and RNA sequencing, immunohistochemistry and in situ hybridization, is used to identify biomarkers that may predict response of cancers to particular targeted therapies.…”
Section: Introductionmentioning
confidence: 99%